The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2gc02089k
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment as a tool for evaluating chemical processes at industrial scale: a review

Abstract: The present paper reviews 47 Life Cycle Assessments (LCA) applied to chemical reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The allocation factor was based on the ratio between the flow rate of the CDP and the flow rate of each scenario of the WMP. This method of defining the flow rate has been discussed and implemented in various publications. , Another example of a similar approach is the consideration of module D within the EN 15804:2012 + A2:2019 for the inclusion of information beyond the cradle-to-gate scope in construction product LCAs. , These allocation factors are presented in Table for 11 different scenarios defined from the operating ranges presented in Wet milling processsection.…”
Section: Methodsmentioning
confidence: 99%
“…The allocation factor was based on the ratio between the flow rate of the CDP and the flow rate of each scenario of the WMP. This method of defining the flow rate has been discussed and implemented in various publications. , Another example of a similar approach is the consideration of module D within the EN 15804:2012 + A2:2019 for the inclusion of information beyond the cradle-to-gate scope in construction product LCAs. , These allocation factors are presented in Table for 11 different scenarios defined from the operating ranges presented in Wet milling processsection.…”
Section: Methodsmentioning
confidence: 99%
“…FT-IR and solid-state 31 P MAS NMR spectroscopic investigations of MCC and P-CNCs were performed to study the structure of P-CNCs. Significantly, the stretching vibration peak of -OH groups at 3400 cm −1 and the C-H symmetrical stretching vibration peak at 2903 cm −1 were observed in the FT-IR spectra of both MCC and P-CNCs (Fig.…”
Section: Structural and Morphological Properties Of P-cncsmentioning
confidence: 99%
“…Life cycle assessment (LCA) is an internationally standardized method to quantitatively analyse the cumulative environmental burdens of products, services and technologies, 29,30 and it significantly benefits the design and optimisation of novel production processes. 31 In the past few years, LCA has been widely used to evaluate the environmental performance of nanocellulose, e.g., CNCs and CNFs. 32 However, there has been no LCA study on P-CNC production, resulting in difficulties in process comparison, adaptation and optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…Life cycle assessment (LCA) is performed to design 27 and optimize 28 novel chemical processes and products, especially at an early stage, 29 in both laboratory and industrial‐scale, 30 by considering the environmental sustainability performance across all stages of a product's life cycle 31 . For example, an early stage LCA study of nanocellulose yarn revealed that wet‐spinning was cleaner than electrospinning, and the efforts on heat recovery and improving solvent exchange presents ecofriendly benefits, which will enable precise optimization in future 32 .…”
Section: Introductionmentioning
confidence: 99%